2008
DOI: 10.2193/2007-291
|View full text |Cite
|
Sign up to set email alerts
|

Space Use and Habitat Selection by Bobcats in the Fragmented Landscape of South‐Central Iowa

Abstract: Historically, bobcats (Lynx rufus) were found throughout the Corn Belt region, but they nearly disappeared from this area due to habitat loss and unregulated harvest that occurred during the century after European settlement. Reports of bobcat occurrences have been increasing in Iowa, USA, and biologists would like to understand the mechanisms enabling bobcats to recolonize this fragmented agricultural landscape. We determined space use and habitat selection of bobcats by radiocollaring 68 bobcats in south‐cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
78
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 26 publications
7
78
2
Order By: Relevance
“…Male bobcats tend to have larger home ranges, move longer distances during the process of dispersal, and exhibit greater competition for space, which makes encounters with roads and urban areas more likely (Sandell 1989, Sunquist and Sunquist 1989, Janecka et al 2006, Tucker et al 2008. Studies of bobcat behavior in California suggest that there is either no difference in male vs. female bobcat use of urbanized areas or that females cross roads and use urbanized areas less than males ).…”
Section: Discussionmentioning
confidence: 99%
“…Male bobcats tend to have larger home ranges, move longer distances during the process of dispersal, and exhibit greater competition for space, which makes encounters with roads and urban areas more likely (Sandell 1989, Sunquist and Sunquist 1989, Janecka et al 2006, Tucker et al 2008. Studies of bobcat behavior in California suggest that there is either no difference in male vs. female bobcat use of urbanized areas or that females cross roads and use urbanized areas less than males ).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all studies of bobcat habitat relationships have concluded that bobcat presence and abundance is influenced by the distribution and characteristics of forested habitat (Woolf et al 2002, Preuss and Gehring 2007), especially at the local scale (Lovallo et al 2001, Constible et al 2006, Tucker et al 2008). However, our analyses and modeling highlight that the quantity and configuration of other habitats, especially perennial grassland cover in association with woodlands, predicted relative abundance of Iowa bobcats at the county scale.…”
Section: Discussionmentioning
confidence: 99%
“…We also calculated metrics at the landscape level, representing the structure of the landscape mosaic, regardless of habitat class (Constible et al 2006). Past research suggested that Iowa bobcats selected forest habitat in their home range twice as often as predicted by random chance, grassland and CRP approximately equal to random chance, and row crop much less than random chance (Tucker et al 2008). Consequently, we assigned edge between forest and row crop a high contrast (0.8), edges between forest and grassland and forest and CRP a moderate contrast (both 0.5), and edge between grassland and CRP a low contrast (0.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…I used compositional analysis methods (as in Chamberlain et al 2003 andTucker et al 2008) to estimate the ratio of used to available habitat for each collared bobcat at three levels: home range to available habitat, core to available, and core to home range. I used a paired t-test to test whether the percent of avocado orchard in the used and available habitats differed.…”
Section: Compositional Analysismentioning
confidence: 99%